MATHEMATICAL MODEL OF TORSIONAL OSCILLATIONS DRILLING COLUMN WITH FLEXIBLE COUPLING IN COMPOSITION - Moisyshyn, V. M.; Vekeryk, V. І.; Landar, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
A generalized mathematical model of the torsional vibrations of the drilling columnis proposed, the composition of which includes support-centering elements, an elastic coupling, and a screw drilling motor. The portable movement of the drilling columnis taken to be a steady rotational movement with a given angular velocity and the relative movement is taken to be oscillations disturbed by the bit. The model allows you to determine the relative and transfer components of the angle of rotation, torque and tangential stress in the cross sections of the column.